PROMOTING GREEN INVESTMENTS IN ORDER TO STRENGTHEN SUSTAINABLE FINANCING - DUDUIАLĂ РОРЕSCU LОRЕNА (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
In the current global context, characterized by interconnected ecological and economic challenges, the promotion of green investments is becoming a strategic priority. This direction not only responds to the need to protect the environment, but also facilitates the transition to a sustainable economic model. By encouraging initiatives that integrate green technologies and innovative solutions, a favorable framework is created for attracting the capital necessary for the development of green infrastructure.